PENYULUHAN DALAM MENGHADAPI PELUANG DAN TANTANGAN ERA REVOLUSI INDUSTRI 4.0 DI YAYASAN MIZAN AMANAH TEBET - Muhammad Firdaus; Rahmawati Yuliyani (Universitas Indraprasta PGRI, 2021)
Alhamdulillah, by looking at the future of rapid and sophisticated development of information technology that does not rule out the possibility of every Indonesian society in general, the teachers and the management of Mizan Amanah in particular get updated information and knowledge, so as not to be outdated and to compete with the community abroad. The purpose of conducting PKM activities within the Mizan Amanah Foundation is to introduce ideas, inovation, and realization of the industrial revolution 4, provide an overview and experience in responding to the digital era, and to use it wisely. In this PKM (Community Service) activity, we use observation and direct interviews as research methods with the management to get information related to daily activities and activities at the Foundation, so that we can get to know the educational background, expertise, and professions of each of them each teacher and administrator. From this research, students are expected to be more open in their insights about information technology and its use, and to use it more wisely in everyday life. This is possible to be able to give positive hope to them in the future, so that they are ready to be able to welcome a better tomorrow.